2018
DOI: 10.23937/2469-5726/1510059
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Macrophages: Potential Key Modulators of Cartilage Damage, Osteophyte Formation and Pain in Knee Osteoarthritis

Abstract: Synovitis is common in knee OA patients and a known contributor to disease incidence and progression. Macrophages are the most common immune cell type present in this inflamed synovial tissue and expectedly contribute both directly and indirectly to OA progression through the induction of inflammatory mediators, growth factors and proteinases, resulting in enhanced cartilage degeneration and osteophyte formation. Furthermore, macrophage infiltration and soluble macrophage products may be associated with pain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 112 publications
(255 reference statements)
0
5
0
Order By: Relevance
“…Macrophages are predominant immune cells that infiltrate IPFPs and synovial tissues of OA patients ( 7 11 , 26 , 27 ). They are highly plastic cells that undergo polarization in response to altered environmental stimuli or pathological conditions ( 11 , 15 ). Many diseases describe macrophages in terms of their M1 vs. M2 polarization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages are predominant immune cells that infiltrate IPFPs and synovial tissues of OA patients ( 7 11 , 26 , 27 ). They are highly plastic cells that undergo polarization in response to altered environmental stimuli or pathological conditions ( 11 , 15 ). Many diseases describe macrophages in terms of their M1 vs. M2 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are a predominant component of mononuclear cell infiltration in synovial tissues and IPFPs and are highly activated in OA ( 7 9 ). Previous research has revealed the correlation between synovial macrophages with several OA pathologies ( 10 , 11 ). A high percentage of synovial macrophages was detected in the synovial tissues of OA patients with moderate-grade synovitis, suggesting the association between macrophages with synovitis ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their functions also vary with physiological and pathological conditions 52 , 53 . Synovial macrophages act as immune cells crucial to the symptomatology and structural progression of OA 54 . These activated macrophages are regulated by a variety of stimulators and can polarize into either M1 or M2 subtypes in synovial tissue, synovial fluid, or peripheral blood 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Synovial-released inflammatory substances can inhibit the chondro-genetic differentiation of MSCs in cartilages, and this is probably related to an excessive prevalence of M1-like macrophages in the lesion [69][70][71][72][73][74] . The modulation of macrophage polarization towards an anti-inflammatory M2 phenotype is of vital importance in the development of regenerative cell therapies for cartilages [74][75][76][77] .…”
Section: Cartilage Tissue Repairingmentioning
confidence: 99%